Persepsi Masyarakat terhadap Kurikulum Pendidikan Anak Usia Dini - Sutjipto -- (Jurnal Pendidikan dan Kebudayaan, 2015)
The purpose of this study is to obtain public perceptions of early childhood education curriculum. The study used a case study approach with positivistic research paradigm and conducted from September to November 2014. Data analysis was performed using simple descriptive analysis in the form of a narrative. The results shows that the issue of curriculum and its implementation is not just the domain of curriculum developers, but also other aspects perceived as significant issues by the community. First, public perceives the importance of the rational of development, the cornerstone of development, strategy and procedure of development, structure and content of the curriculum, implementation strategies, and the existence of books and equipment in the context of curriculum design. Second, regarding the presence of the developed early childhood education curriculum, society strongly perceives that the document has been considering various aspects to the growing of interest for early childhood in practice of reading, writing, speaking, socializing/making friends, eating and drinking together, discipline, manners , faith, and playing activities, singing, marching, and exercise. Third, the implementation of the curriculum is perceived by society as an in need of harmonies cooperation among educational institutions, public, and educational supervisors in the region, especially in terms of teaching staff, procurement of books and equipment and other support resources.